A Critical Discourse Analysis of Selected Poems of “Maya Angelou”: (“Equality”, “Cage Birds” and Other Poems as Examples) - Bushra Osman Sidiq; Media Rafiq Majeed (Journal of Arts, Literature, Humanities and Social Sciences, 2022)
Language users’ choices of linguistic forms and expressions are usually guided by their thoughts, feelings, attitudes and their stance in the real world. Language, according to CDA, is never neutral and it always has some implications of the world that surrounds us. Critical studies are concerned with scrutinizing power relations, ideological manifestations and hegemony in social practices. The current paper is a critical discourse analysis (CDA) of selected poems of Maya Angelou, who is an African American poet, memoirist, and civil rights activist. It sheds light on the figurative language of the poems that are selected randomly for the purpose of analysis. The five selected poems: "Still I Rise, Equality, Caged Bird, On the Pulse of Morning and Phenomenal Woman." are analyzed based on Fairclough’s model of CDA. The study tries to show the implicit figurative language in the poems and identify different figures of speech that have implicit meaning in the poems. It also examines how figurative language is used to enhance the meaning of the poems and communicating the ideas more effectively. .